2022
DOI: 10.28918/muwazah.v13i2.4154
|View full text |Cite
|
Sign up to set email alerts
|

Permissive Attitudes to Domestic Violence on Women in Indonesia

Abstract: Violence against women occurs in almost all countries and has become a global issue that is often reviewed and discussed at various seminars. The United Nations defines violence against women as "Any act of gender-based violence that results in or is likely to cause physical, sexual, or mental damage or suffering to women, including the threat of such actions, the coercion or deprivation of liberty arbitrarily, whether occurring in the public sphere and private life. The purpose of this analysis is to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies have shown that parents with higher levels of education tend to be better able to provide good sex education to their children, which can reduce the risk of sexual abuse in early childhood (Ratnasari Risa Fitri and Alias M, 2016;Purnamasari and Herfanda, 2019), extramarital pregnancy and sexually transmitted diseases in adolescents (Revany Mahardika Wijaya, 2021). However, there are still many parents who have difficulty in providing sex education (Nadar, 2017;Oktriyanto et al, 2021). This can be due to lack of knowledge or due to social and cultural constraints (Putra, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that parents with higher levels of education tend to be better able to provide good sex education to their children, which can reduce the risk of sexual abuse in early childhood (Ratnasari Risa Fitri and Alias M, 2016;Purnamasari and Herfanda, 2019), extramarital pregnancy and sexually transmitted diseases in adolescents (Revany Mahardika Wijaya, 2021). However, there are still many parents who have difficulty in providing sex education (Nadar, 2017;Oktriyanto et al, 2021). This can be due to lack of knowledge or due to social and cultural constraints (Putra, 2018).…”
Section: Introductionmentioning
confidence: 99%